Procedures for Bullying or Harassment Disputes in the Workplace (Global Journal of Human-Social Science, 2013)
These procedures should regulate the intervention in workplace bullying or harassment disputes of any kind (whether sexual harassment or bullying) suffered by a person from other people who are working in the same company or workplace or by third parties. We need them because everybody (company and workers) should know how to act quickly and safely when such a kind of conflicts arises, without being necessary to improvise a response before that particularly delicate situation. The purpose of the procedure is to avoid and prevent the risk of harassment or bullying by early detection of the circumstances that can generate it and adopt appropriate preventive and corrective measures. When a bullying behaviour has been verified or has actually occurred, other disciplinary or disputes proceedings have to be approached.